The concept of revolution and Liberation of Leonardo Boff' Thinking, 1980-2000 - Barrientos Valverde, Jorge (2023)
During the Cold War period, the Liberation Theology movement in Latin America became one of the most important expressions of popular movements inspired on the one hand by primitive Christianity, and on the other hand by the struggles of Marxism. Through this articulation they managed to build a whole school of thought in the region. This paper investigates some key concepts of one of the main exponents of this movement: Leonardo Boff. In this line, the research starts from theoretical elements of conceptual history to approach the meaning that the concept of revolution had for Boff and then the term of liberation between 1980 and 2000 with the aim of visualizing the changes in meaning and treatment of themes that the historical break that took place between the eighties and the nineties had for the author.